3D Graphene Network Encapsulating Mesoporous ZnS Nanospheres as High‐Performance Anode Material in Sodium‐Ion Batteries. Issue 12 (11th May 2018) - Hu, Liang; Hu, Xiang; Lin, Zhoubin; Wen, Zhenhai
Abstract: Here, we reported the synthesis of a three‐dimensional (3D) interconnected network nanostructure of reduced graphene oxide (rGO), enwrapping mesoporous ZnS nanospheres (m‐ZnS NSs@rGO). The synthesis is implemented by a simple gelatin‐assisted hydrothermal reaction followed by self‐assembly between mesoporous ZnS NSs and rGO. As a result of the synergic effect of the special nanostructure of ZnS nanospheres and rGO enwrapping, the m‐ZnS NSs@rGO composite exhibits favorable features as anode material in sodium‐ion batteries. These features include good cycling stability (513 mAh g −1 at 0.1 A g −1 after 80 cycles) and good rate capability (320 mAh g −1 at 1 A g −1 ). The 3D conductive structure, in conjunction with the mesoporous ZnS nanoparticles, provide advantageous features to the hybrids to buffer volume expansion/contraction upon the sodiation/desodiation process and facilitate mass (ions and electron) transportation and electron transfer. Abstract : Wrapped up : Zinc sulfide nanospheres enwrapped in a three‐dimensional network of reduced graphene oxide (rGO) are synthesized. Characterization of the composite material reveals a synergistic effect of the mesoporous nanostructure of the ZnS spheres and rGO enwrapping, leading to favorable features for the application as anode material in sodium‐ion batteries. These features include a good cycling stability and a good rate capability.